Agroclimatic zoning of the Brazilian state of Mato Grosso for the production of soybean seeds of early cultivars - Dielle Carmo de Carvalho Neres; Ricardo Santos Silva Amorim; Maria Cristina de Figueiredo e Albuquerque; Gilda Pizzolante de Pádua; José de Barros França-Neto (Journal of Seed Science)
Abstract: The objective of this work was to carry out the agroclimatic zoning of the Brazilian state of Mato Grosso, in order to identify the regions with the best climatic conditions for producing seeds with high quality of early soybean cultivars. For this purpose, the average monthly temperature data from 11 conventional and 34 automated meteorological stations were used. Due to the low number of stations with data temperature available, this variable was estimated using spatial regression equations, having latitude, longitude and altitude as input variables. Regions with high or low climatic risk were defined according to the average temperatures observed in January and February. The following three categories were established: favorable (≤ 24 °C); moderately favorable (24.1 to 25 °C) and slightly favorable (≥ 25.1 °C). For the material confection, map usage, and geographical data compilation, the inverse distance squared weighted interpolation method was applied. The ArcGIS system was employed to compose the thematic map, in which the best areas for producing seeds of early soybean cultivar were marked. Most of the Southeastern, and Western regions of Mato Grosso were considered to be favorable for producing high quality seeds of early soybean cultivars (average temperature ≤ 24 °C).